2020
DOI: 10.1002/anie.202006435
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Electrofreezing of Super‐Cooled Water on Surfaces of Pyroelectric Crystals is Triggered by Trigonal Planar Ions

Abstract: Electrofreezing experiments of super‐cooled water (SCW) with different ions, performed directly on the charged hemihedral faces of pyroelectric LiTaO3 and AgI crystals, in the presence and in the absence of pyroelectric charge are reported. It is demonstrated that bicarbonate (HCO3−) ions elevate the icing temperature near the positively charged faces. In contrast, the hydronium (H3O+) slightly reduces the icing temperature. Molecular dynamics simulations suggest that the hydrated trigonal planar HCO3− ions se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…This implies that ions concentrated at the charged surfaces, and the way they interact with the water molecules will determine their ability to enhance icing. A structural model that describes how ions of carbonic acid are responsible for electrofreezing is presented in the subsequent paper …”
Section: Figurementioning
confidence: 99%
“…This implies that ions concentrated at the charged surfaces, and the way they interact with the water molecules will determine their ability to enhance icing. A structural model that describes how ions of carbonic acid are responsible for electrofreezing is presented in the subsequent paper …”
Section: Figurementioning
confidence: 99%
“…Leslie and Meir (Figure 1) have been fortunate to work with many other great scientists and continue doing so. [7,8] An open discussion about their Passion and Chemistry with Prof. Ehud Keinan, President of the Israel Chemical Society and member of the Wolf Council, is available on YouTube. [9] Although not inclusive, they thank their collaborators and students for being part of their scientific journey.…”
Section: All Good Wishes Jackmentioning
confidence: 99%
“…Further work found that both planar trigonal negative nitrate and positive guanidinium ions elevate the freezing temperature of water, when accumulated at the interfacial water layers near the positive or negative charged surfaces, respectively. In contrast, the nontrigonal chloride ions reduce the freezing temperature …”
mentioning
confidence: 96%
“…Despite comprehensive investigations during the years, the mechanism of this electrofreezing is still under debate. Some reports deny the existence of the effect, , whereas others maintain that electric fields can either reduce or elevate the icing temperature of SCW. In order to gain additional insight into the electrofreezing mechanism, in particular, to disentangle electric and geometric effects, we capitalized on the unique properties of polar crystals. Such crystals exhibit pyroelectricity, the derivative of the spontaneous polarization with temperature, and develop positive and negative charges at opposite hemihedral surfaces during a temperature change.…”
mentioning
confidence: 99%
See 1 more Smart Citation